Formation and development of foreign language grammatical competence of technical university students with the help of Padlet Internet service - Riabtseva O. M. (Pedagogy, Psychology, Society, 2022)
The author of the article analyzes the didactic and technical possibilities of using Padlet Internet service to organize students' independent work in the study of grammar topic "Vorgangspassiv". The author concludes that Padlet Internet service is the effective tool for forming and developing foreign language grammar competence and increasing students' motivation for learning a foreign language. Online service Padlet allows the teacher to clearly structure the material, connect other digital tools, makes the work of students transparent. The use of this work format corresponds to the ideas of differentiated approach in learning, allows you to implement in practice the principles of personal orientation and autonomy of students, allows students to get a guaranteed positive result.
Keywords: information and communication technologies; информационно-коммуникативные технологии; иноязычная грамматическая компетенция; интернет-сервис Padlet; интерактивные упражнения; foreign language grammatical competence; Padlet Internet service; interactive exercises